PENGARUH APLIKASI MOBILE MINDFULNESS (MM) TERHADAP STRES KERJA PERAWAT - Faridah, Ida; Afiyanti, Yati; Damayanti, Tia (Nusantara Hasana Journal, 2022)
Stress is the cause of many diseases in modern society. Mobile mainfulness-based stress reduction is one way to reduce the stress level experienced by a person. The MM application is expected to be able to control stress levels. The purpose of this study is to see the effect of using the MM application on work stress in nurses. Research design: quasi-experimental (pre test and post test). Data analysis in this study used univariate and bivariate analysis. Results: from the results of the intervention to 112 respondents, the average value of the pre-test was 71.4% and the post-test was 42.9% with a P value of <0.05. There is an Influence of the MM Mindfulness Mobile Application on Nurse Work Stress in Tangerang Regency. Â